11. Ägyptologische Tempeltagung : the discourse between tomb and temple - Coppens, Filip,; Vymazalová, Hana, (Konigtum, Staat und Gesellschaft fruher Hochkulturen ;, 2020)
This volume of the book series Königtum, Staat und Gesellschaft früher Hochkulturen contains the proceedings of the eleventh international conference dedicated to the ancient Egyptian temple in all its aspects, which was hosted by the Czech Institute of Egyptology, Faculty of Arts, Charles University in Prague in May 2017. The main theme of the meeting, the "Discourse between Tomb and Temple" revolved around the many diverse types of interaction that existed between two crucial and tangible expressions of ancient Egyptian thought, belief and culture. Ranging from the Old Kingdom to the era of Roman presence, the fourteen papers in this volume present, analyse and interpret evidence expressed in art, architecture, language, ritual, funerary and other practices, with a spotlight on relations, connections and exchanges between temple and tomb and its development and changing nature over time. This includes topics related to the transmission and exchange of specific textual corpora in addition to individual texts, decorative patterns or architectural elements as well as the interchangeability of rituals. Overall, the papers indicate incontestable distinctions between tomb and temple as well as substantial commonalities. These various forms of exchanges and interactions are moreover not static, but appear to develop and intensify over time, especially from the era of the New Kingdom onward.